2021
DOI: 10.1016/j.phro.2021.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interfractional target motion in locally advanced cervical cancer patients treated with spot scanning proton therapy using an internal target volume strategy

Abstract: Background and purpose The more localized dose deposition of proton therapy (PT) compared to photon therapy might allow a reduction in treatment-related side effects but induces additional challenges to address. The aim of this study was to evaluate the impact of interfractional motion on the target and organs at risk (OARs) in cervical cancer patients treated with spot scanning PT using an internal target volume (ITV) strategy. Methods and materials For ten locally adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…After considering, but not limited to the effects of different radiation techniques, our study showed that the implementation of ITV was an independent favorable prognostic factor for OS and PFS. It is worthy to mention that in one recent study 18 by Niyoteka et al, they found that it was not enough to ensure adequate dose coverage in the high‐risk CTV even though using the ITV concept. There is no doubt that not only the ITV delineation method, but the bladder volume also played an important role in the treatment of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After considering, but not limited to the effects of different radiation techniques, our study showed that the implementation of ITV was an independent favorable prognostic factor for OS and PFS. It is worthy to mention that in one recent study 18 by Niyoteka et al, they found that it was not enough to ensure adequate dose coverage in the high‐risk CTV even though using the ITV concept. There is no doubt that not only the ITV delineation method, but the bladder volume also played an important role in the treatment of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistically significant difference in survival analysis between IMRT and 3DCRT groups in our study, which is the same as several prospective randomized studies 24,26,29 or meta-analysis. 25 Based on the concept of ITV proposed in ICRU62, 30 a large amount of studies 11,12,15,[17][18][19][20][21][22] mainly concentrated on organ motion or contouring margins using the ITV delineation method. However, to our knowledge, there is no study comparing the prognostic difference between the ITV group and the N-ITV group in single radiotherapy techniques such as IMRT and 3DCRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients' Clinical Stages. Before treatment, FIGO staging (2009) [12] and MRI staging [13] were adopted for patients, and the results from the two staging methods were recorded.…”
Section: Cd105mentioning
confidence: 99%